Regulation of AtKUP2 Expression by bHLH and WRKY Transcription Factors Helps to Confer Increased Salt Tolerance to Arabidopsis thaliana Plants - Rajappa, Sivamathini; Krishnamurthy, Pannaga; Kumar, Prakash P. (Frontiers in Plant Science, 2020)
Potassium transporters play an essential role in maintaining cellular ion homeostasis, turgor pressure and pH which are critical for adaptation under salt stress. We identified a salt responsive Avicennia officinalis KUP/HAK/KT transporter family gene, AoKUP2 that has high sequence similarity to its Arabidopsis orthologue AtKUP2. These genes were functionally characterized in mutant yeast cells and Arabidopsis plants. Both AoKUP2 and AtKUP2 were induced by salt stress and AtKUP2 was primarily induced in roots. Subcellular localization revealed that AoKUP2 and AtKUP2 are localized to the plasma membrane and mitochondria. Expression of AtKUP2 and AoKUP2 in Saccharomyces cerevisiae mutant strain (BY4741 trk1Δ::loxP trk2Δ::loxP) helped to rescue the growth defect of the mutant under different NaCl and K+ concentrations. Furthermore, constitutive expression of AoKUP2 and AtKUP2 conferred enhanced salt tolerance in Arabidopsis indicated by higher germination rate, better survival and increased root and shoot length compared to the untreated controls. Analysis of Na+ and K+ contents in the shoots and roots showed that ectopic expression lines accumulated less Na+ and more K+ than the WT. Two stress-responsive transcription factors, bHLH122 and WRKY33 were identified as direct regulators of AtKUP2 expression. Our results suggest that AtKUP2 plays a key role in enhancing salt stress tolerance by maintaining cellular ion homeostasis.